Fictivity in Vogue: a cognitive-functional categorization of fictive speech acts in a fashion corpus using corpus linguistics - Rossini Martins Cardoso, Raquel; Nunes Pereira Oliva, Katherine; Araújo e Castro, Rodrigo; Zuppardi, Maria Carolina; Malta, Izabella Rosa (Universidade do Estado do Rio de Janeiro, 2021)
Fashion pervades different instances of culture, ranging from clothes to language and behavior. In this paper, we analyze the occurrence of three fictive speech categories (PASCUAL, 2014) as storytelling strategies in sections of North American Vogue magazine. This paper aims at investigating through a mixed-method approach cognitive-functional categories of fictive speech acts based on a corpus analysis of a corpus with fashion texts. We collected 200 texts from Vogue magazine (printed edition) from 2015 to 2018. In a sample of 60 texts, sentential (SENT), intra-sentential (INTRA) and inter-sentential (INTER) fictive acts were manually identified and categorized in each text through tags. The quantitative analysis mapped the counts of each category per year and per text and the qualitative in-depth analysis investigates instances from each category and their interpretation in the light of Fashion and cognitive and corpus linguistics theories. The findings show that the occurrence of the categories of fictive speech acts varies per year with opposing trends, though they tend to co-occur in the same texts. Therefore, fictive speech acts function as recurrent discursive strategies to foster a conversational environment in texts from Vogue magazine.